1981
DOI: 10.1152/jappl.1981.51.4.788
|View full text |Cite
|
Sign up to set email alerts
|

Effect of beta-adrenergic blockade on respiratory and metabolic responses to exercise

Abstract: The responses to oral propranolol (80 mg) and placebo were compared in normal subjects during three studies on a cycle ergometer (progressive exercise and two 5-min constant work rate studies at 50 and 70% maximum). Heart rate (HR), ventilation (VE), CO2 output (VCO2) and O2 uptake (VO2) were measured in each study and metabolites in venous blood in the 70% study. Propranolol reduced HR in all studies and endurance time during progressive exercise. During constant-work-rate exercise the changes with propranolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
34
1

Year Published

1984
1984
2013
2013

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 0 publications
6
34
1
Order By: Relevance
“…The decrease of submaximal Vo, afteradrenoceptor blockade found in the present study is consistent with almost all the published data (Pearson et al, 1979;Twentyman et al, 1981;Tesch & Kaiser, 1983;Butland et al, 1983;Sue et al, 1983), while the concomitant changes we have found in Vco, and VE are in agreement with only some of them (Twentyman et al, 1981;Butland et al, 1983;Sue et al, 1983).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…The decrease of submaximal Vo, afteradrenoceptor blockade found in the present study is consistent with almost all the published data (Pearson et al, 1979;Twentyman et al, 1981;Tesch & Kaiser, 1983;Butland et al, 1983;Sue et al, 1983), while the concomitant changes we have found in Vco, and VE are in agreement with only some of them (Twentyman et al, 1981;Butland et al, 1983;Sue et al, 1983).…”
Section: Discussionsupporting
confidence: 94%
“…The lack of changes on maximum work rate and PER is a finding apparently conflicting with most previously published reports (Pearson et al, 1979;Anderson et al, 1979;Rusko et al, 1980;Twentyman et al, 1981;Tesch & Kaiser, 1983;Petersen et al, 1983). These studies were carried out on subjects with high exercise capacity as a result of the prevalence of males, often physically fit and exercise trained.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In more recent investigations, inferences have been drawn regarding the metabolic effects of P-adrenoceptor blocking drugs from respiratory gas exchange data (Pearson et al, 1979;Twentyman et al, 1981). Most recently, Petersen and colleagues (1983) have claimed that alterations in respiratory gas exchange during exercise after P-adrenoceptor blockade were minimal (Petersen et al, 1983 (1982) (acebutolol, pindolol).…”
Section: Introductionmentioning
confidence: 99%